THE EFFECTIVENESS OF DIARY WRITING IN IMPROVING UNIVERSITY STUDENTS’ ASSERTIVE ATTITUDES - Eko Kuntarto (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aimed to apply diary writing as a therapy for low-assertive students. This study employed the Core Conflictual Relationship Theme (CCRT) method developed by Lester Luborsky. The data were collected using diary as an elicitation medium and analyzed using the Garnefski Emotion-Cognitive Regulation Questionnaire (CER). The results showed that(1) student low assertiveness could be improved through expressive writing therapy using a diary as the medium; (2) diary as a therapeutic medium was effective in improving student low assertiveness because diary writing tasks can be distinguished based on CCRT and CER; (3) there was a difference between male and female assertiveness patterns; (4) subjects in the category were easier to change towards normal assertiveness with diary writing therapy compared to subjects in the LSE category.